Competences of the administrator’s graduate profile in a global context, a review of the literature: Competencias del perfil de egreso del administrador en un contexto global, una revisión de la literatura - Tassara Salviati, Carlos Francisco José (2020)
In an increasingly integrated and challenging world, companies require administrators whoare able to cope with a globalized and highly competitive business environment. In thatsense, the objective of the research is to establish the competences of the administrator’sgraduate profile to perform in a global context. To this aim, a qualitative design researchof documentary type was developed, using as a source of information scientific papersindexed in the Google Academic database. An important finding is that genericcompetences such as teamwork, strategic leadership, adaptation to change, technologymanagement and ability to interact in multicultural environments, among others, are morevalued by employers than specific competences.